Relationship between low bone mineral density and fractures with incident cardiovascular disease: a systematic review and meta-analysis - Veronese, N; Stubbs, B; Crepaldi, G; Solmi, M; Cooper, C; Harvey, N; Reginster, J; Rizzoli, R; Civitelli, R; Schofield, P; Maggi, S; Lamb, S (American Society for Bone and Mineral Research, 2017)
An increasing evidence base suggests that low bone mineral density (BMD) and fractures are associated with cardiovascular disease (CVD). We conducted a systematic review and meta-analysis summarizing the evidence of low BMD and fractures as risk factors for future CVD. Two independent authors searched major databases from inception to August 1, 2016, for longitudinal studies reporting data on CVD incidence (overall and specific CVD) and BMD status and fractures. The association between low BMD, fractures, and CVD across longitudinal studies was explored by calculating pooled adjusted hazard ratios (HRs) ±95% confidence intervals (CIs) with a random-effects meta-analysis. Twenty-eight studies (18 regarding BMD and 10 fractures) followed a total of 1,107,885 participants for a median of 5 years. Taking those with higher BMD as the reference, people with low BMD were at increased risk of developing CVD during follow-up (11 studies; HR = 1.33; 95%CI, 1.27 to 1.38; I2  = 53%), after adjusting for a median of eight confounders. This finding was confirmed using a decrease in one standard deviation of baseline BMD (9 studies; HR = 1.16; 95% CI, 1.09 to 1.24; I2  = 69%). The presence of fractures at baseline was associated with an increased risk of developing CVD (HR = 1.20; 95% CI, 1.06 to 1.37; I2  = 91%). Regarding specific CVDs, low BMD was associated with an increased risk of developing coronary artery disease, cerebrovascular conditions, and CVD-associated death. Fractures at baseline was associated with an increased risk of cerebrovascular conditions and death due to CVD. In conclusion, low BMD and fractures are associated with a small, but significant increased risk of CVD risk and possibly death. © 2017 American Society for Bone and Mineral Research.